Dye Sensitized Solar Cell Menggunakan Ekstrak dari Bunga Pukul Empat (Mirabilis jalapa) Merah dan Kuning - Hamdani, Mochammad Luthfi (ALKIMIA, 2021)
Four o’clock flowers contain betalain compound namely betacyanin and betaxanthin. This compound is used as sensitizer on dssc. This study used water as a solvents with pH variations of 2, 4, and 6 for the extraction of betalain compounds from four o'clock flowers. Molecular characterization of compounds using Uv-Vis spectrophotometer to determine the wavelength and FTIR to determine the functional groups. The HOMO and LUMO analysis using a Cyclic Voltametery. This study generated absorbance to red and yellow four o'clock flowers extract is 532.50 nm which is betacyanin and 473.30 nm which is betaxanthin. FTIR analysis both of dyes produce wave number 3750-3000 cm-1 showed the presence of hydroxyl (O-H) and 1675-1500 cm-1, which showed the presence of alkenes. The HOMO and LUMO analysis using cyclic voltammetry of betacyanin extract at pH 2 were -3,497 eV and -6,012 eV and betaxanthin were -3,623 eV and -5,803 eV. DSSC performance using betacyanin and betaxanthin dye showed an efficiency value of 0.208% and 0.0036%. Results showed that the extract betacyanin and betaxanthin of red and yellow four o'clock flowers have shown a good sensitizer agents in DSSC. Keywords: Betacyanin, Betaxanthin, DSSC, Efficiency